2013
DOI: 10.7763/ijet.2013.v5.545
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Induced Carbon from Waste Palm Kernel Shell Activated by Phosphoric Acid

Abstract: Abstract-Activated carbon has been known as an excellent adsorbent which has been widely used due for its large adsorption capacity and low cost. In Malaysia, palm kernel shell is one of the main agriculture wastes obtained from palm oil industries. In this study, the palm kernel shell-based activated carbon was prepared via microwave-induced activation process using phosphoric acid, H Index Terms-Activated carbon, palm kernel shells, microwave-induced, phosphoric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 7 publications
1
14
0
Order By: Relevance
“…The raw material (50 g) was ground and sieved to particle sizes between 75 and 250 lm, soaked and impregnated with 10 mL of 30 wt% of phosphoric acid, H 3 PO 4 , at room temperature as a pre-treatment procedure with the ratio of PKS to acid as 1:1. The purpose of the pre-treatment was to destroy the lignin and cellulose present in the raw PKS [29]. The sample was left impregnated for 24 h, washed with distilled water and dried at room temperature.…”
Section: Preparation Of Activated Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…The raw material (50 g) was ground and sieved to particle sizes between 75 and 250 lm, soaked and impregnated with 10 mL of 30 wt% of phosphoric acid, H 3 PO 4 , at room temperature as a pre-treatment procedure with the ratio of PKS to acid as 1:1. The purpose of the pre-treatment was to destroy the lignin and cellulose present in the raw PKS [29]. The sample was left impregnated for 24 h, washed with distilled water and dried at room temperature.…”
Section: Preparation Of Activated Carbonmentioning
confidence: 99%
“…and 50% wt/wt., respectively [29]. The pre-treated PKS was again treated using dilute acid (10, 20 and 30% wt/wt H 3 PO 4 ) to determine the resulting surface area at which if the surface area obtained using dilute acid is considered high, thus the utilization of concentrated acid can be reduced and the experiment will be more cost-effective.…”
Section: Preparation Of Activated Carbonmentioning
confidence: 99%
“…Despite the finding that pyrolysis at 500˝C leads to a low degree of carbonization [21,22], the present study showed acceptable electricity generation with AC ( Figure 2) and less internal resistance than with CP ( Figure 3). …”
Section: Performance Of Ac Relative To Cpmentioning
confidence: 81%
“…This electrode material can be produced in rural communities and would require little education. In the AC form, palm kernel shells have high porosity, large internal surface area and high strength, which are important physical properties for an MFC [20][21][22]. The pore volumes have been found to 0.003-0.01 cm 3 /g of mesopores and to 0.011-0.11 cm 3 /g of micropores [20].…”
Section: Introductionmentioning
confidence: 99%
“…Based on research [40] relatively to conventional heating Processes, microwaves activated carbon developed from apple pulp and apple peel using phosphoric acid as activating agent show a high BET surface areas and mesopore volumes after a shorter activation time due to differences in the type of heat transfer between these two processes. In addition, a group of researcher [41] carried out an investigation using waste palm kernel shells and was able to obtain microwave-induced high surface area; chemical activated carbon successfully developed using phosphoric acid. The microwave developed activated carbons were characterized using Fourier Transform Infrared Spectroscopy, Nitrogen Gas Adsorption analysis and Thermal Analysis respectively.…”
Section: Steps Involved In Development Of Activated Carbonmentioning
confidence: 99%